Political ignorance and the internet - Irene Bertschek; David F. Müller (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We examine the link between Internet usage and political ignorance. We construct a novel Index as a direct measure of individuals' indifference with respect to political issues which determines the degree of individual political ignorance. Our econometric analysis is based on a rich data set consisting of six surveys of individuals covering the time period 2001 to 2014 and being representative for the German electorate. The empirical results show that in the earlier years of Internet diffusion there is a negative link between using the Internet and political ignorance. This link changes sign in later years of Internet diffusion. We discuss potential explanations of this observed change in the link such as information overload and the increase in heterogeneity of Internet users.
Keywords: D80; O33; 330; Internet; information cost; indifference index; political ignorance